2005
DOI: 10.14411/fp.2005.013
|View full text |Cite
|
Sign up to set email alerts
|

Multinucleate host cells induced by Vittaforma corneae (Microsporidia)

Abstract: Abstract. The microsporidium Vittaforma corneae (Shadduck, Meccoli, Davis et Font, 1990) develops within the target cell cytoplasm. In the present study, green monkey kidney (E6) cells infected at 30°C, 35°C or 37°C with V. corneae developed enlarged multinucleate structures of up to 200 µm in any horizontal dimension made up either of a single cell or of multiple fused cells. A number of epithelial cell types (SW-480, HT-29, Caco-2 and HCT-8) were infected with V. corneae but did not induce the same highly or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…One study of a human microsporidian did elicit some xenomalike growth within E6 cells (Leitch et al 2005). One study of a human microsporidian did elicit some xenomalike growth within E6 cells (Leitch et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One study of a human microsporidian did elicit some xenomalike growth within E6 cells (Leitch et al 2005). One study of a human microsporidian did elicit some xenomalike growth within E6 cells (Leitch et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of mouse macrophages in primary culture but not of a mouse macrophage cell line with interferon gamma (IFNγ) inhibited E. cuniculi replication (Jelinek et al 2007). On the other hand, the reorganization of microbutules and induction of multinucleation in green monkey cell line E6 by V. cornea might be away for the parasite to be protected from the host immune response (Leitch et al 2005). To date, this has only been documented in vitro.…”
Section: Culturing Microsporidia Of Human Diseasesmentioning
confidence: 99%
“…Determining between the two is of interest because the secretion pathway is likely a major route for parasite−host interactions in this system: any protein secreted by a microsporidian is actually released into the parasitophorous vacuole or the host cytoplasm, and infection by many microsporidia is known to produce a dramatic effect on the organisation and activity of the host cell. [16][17][18] To determine if microsporidian Sec complexes include Sec61β, we used a genome sequence survey of a second microsporidian species, Antonospora locustae, and based on genomic position, secondary structure analysis, as well as localisation and complementation in yeast, found that a highly divergent form of Sec61β is indeed present in both microsporidia.…”
Section: Introductionmentioning
confidence: 99%